Investigating the Friction Coefficient of Titanium Bolts with Vegetable Oils as Lubricants - Dario Croccolo; Massimiliano De Agostinis; Stefano Fini; Muhammad Yasir Khan; Mattia Mele; Giorgio Olmi; Chiara Scapecchi; Muhammad Hassaan Bin Tariq (Engineering Proceedings)
Threaded fasteners are one of the most important joining techniques, especially due to their ease of mounting and dismounting. These are essentially friction joints; therefore, friction coefficients between the surfaces play a critical role in the correct mounting of the threaded fasteners. Materials and lubrication conditions are the major factors that can affect the correct preload of the threaded fasteners. Particularly, when shifting from steel to titanium fasteners to achieve a high strength-to-weight ratio, the friction shift is very significant. Researchers have studied varying levels of lubrication to achieve optimum friction conditions. VG46 has been used most in the literature; however, its non-renewable nature necessitates the use of another alternative that is good for the environment and can cause a reduction in pollution in the environment. For this reason, in the present study, castor oil and fractionated coconut oil have been used for Ti bolts to achieve low friction coefficients. Torque tension tests have been performed on the Ti bolts using the different lubricants mentioned above and friction coefficients at the underhead and the threaded portions are compared with the commercial VG46 lubricant. Castor oil shows good performance compared to the other lubricants tested in terms of underhead friction coefficients, whereas the thread friction coefficients remain almost the same in all the lubrication conditions.